Block copolymer self-assembly in ionic liquids. Issue 39 (15th August 2018) - Tamate, Ryota; Hashimoto, Kei; Ueki, Takeshi; Watanabe, Masayoshi
Abstract : Recent developments in block copolymer self-assembly in ionic liquids are reviewed from both fundamental and applied aspects. Abstract : Ionic liquids (ILs), solely composed of cations and anions, are regarded as a novel class of promising liquids, potentially applicable to energy devices, reaction media, separation materials, etc. ILs have also attracted great attention as new media for molecular self-assembly, capable of producing novel soft materials with unique features never observed for conventional soft materials containing organic and aqueous solvents. In this review, we focus on recent developments in block copolymer (BCP) self-assembly in ILs. Self-assembled structures formed by dilute and concentrated BCP solutions in ILs are discussed in detail. Ion gels formed by BCP self-assembly have received special interest because they exhibit excellent physical properties of tunable viscoelasticity and solution processability without impairing the intrinsic properties of ILs, such as nonvolatility, nonflammability, and high ionic conductivity. Applications of ion gels based on BCP self-assembly for electric double layer capacitors, lithium-ion batteries, and electroactive soft actuators are also addressed.